Pengembangan Aplikasi Analisis Struktur Rangka Batang Bidang Berbasis Antarmuka Pengguna Grafis - Frans, Richard; Tjiwanda, Antonius Agusto; Kalangi, Hendry; Thioritz, Stevy; Mursalim, Mursalim (JNSTA ADPERTISI JOURNAL, 2022)
This research develops an analysis structure program for plane truss structure using stiffness matrix method and based on graphical user interface. The program is developed using GUIDE feature from MATLAB R2014 software. The features that were developed of this program is to analyze the reaction forces, internal forces and global displacement for plane truss structure. There are 3 (three) types of plane structures were considered. Reaction forces, internal forces and global displacement which obtained from the program were compared to commercial program which is ETABS 2016. Based on the result, there is not significantly different between the program which developed and ETABS 2016 for reaction forces, internal forces or global displacement. Therefore, the program can be an alternative software to analyze plane truss structure